2006
DOI: 10.1103/physrevlett.97.037001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Impurities in a Two-Band Superconductor: A Point-Contact Study of Mn-SubstitutedMgB2Single Crystals

Abstract: We present the first results of directional point-contact measurements in Mg1-xMnxB2 single crystals, with x up to 0.015 and bulk Tc down to 13.3 K. The order parameters Deltasigma and Deltapi were obtained by fitting the conductance curves with the two-band Blonder-Tinkham-Klapwijk model. BothDeltapi and Deltasigma decrease with the critical temperature of the junctions TAC, but remain clearly distinct up to the highest Mn content. Once analyzed within the Eliashberg theory, the results indicate that spin-fli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 24 publications
(33 reference statements)
2
44
0
Order By: Relevance
“…Similar conclusions have been drawn from a point-contact spectroscopy. 41 There are at least two mechanisms possible for the reduction of T c in MgB 2 substituted with magnetic isovalent ions. One is the impurity-induced ͑nonmagnetic͒ interband scattering and the second is the magnetic pair-breaking effect.…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions have been drawn from a point-contact spectroscopy. 41 There are at least two mechanisms possible for the reduction of T c in MgB 2 substituted with magnetic isovalent ions. One is the impurity-induced ͑nonmagnetic͒ interband scattering and the second is the magnetic pair-breaking effect.…”
Section: -12mentioning
confidence: 99%
“…[37][38][39][40] Concomitantly to this work, the Mn-substituted MgB 2 crystals from the same batches have been studied by a pointcontact spectroscopy. 41 In our previous studies we have reported on the crystallographic and superconducting properties of MgB 2 single crystals substituted with Al and C ions. 31,36 These electrondoping non-magnetic substitutions result in a similar moderate decrease of the superconducting transition temperature, T c , and in a different influence on the upper critical field.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] It is therefore an interesting question how the presence of these two gaps influences the structure of Shiba states. Although a series of experimental 19,20 and theoretical 21,22 investigations have been recently completed for MgB 2 doped with nonmagnetic as well as magnetic impurities, no experimental or theoretical study has been completed for the local electronic structure of a single magnetic impurity in this compound. This paper now provides a detailed theoretical discussion of the single magnetic impurity problem in MgB 2 and other superconductors where the multiple degrees of freedom of the conduction electrons and the impurity could lead to experimentally observable consequences.…”
Section: Introductionmentioning
confidence: 99%
“…two on single crystals [11,12] and the other on bulk samples [13]. The most remarkable feature of Mn substitution is that it exhibits the most rapid decrease in transition temperature.…”
Section: Introductionmentioning
confidence: 98%